The Effect of Cold Plasma Pretreatment on Water-Suspended Herbs Measured in the Content of Bioactive Compounds, Antioxidant Activity, Volatile Compounds and Microbial Count of Final Extracts - Ewelina Pogorzelska-Nowicka; Monika Maria Hanula; Marta Brodowska-Trębacz; Elżbieta Górska-Horczyczak; Urszula Jankiewicz; Tomasz Mazur; Monika Marcinkowska-Lesiak; Andrzej Półtorak; Agnieszka Wierzbicka (MDPI AG, 2021)
Cold plasma is a new technology of promising potential to use as a part of technological extraction lines constructed to implement green chemistry solutions or simply to reduce resources in solvent-based extraction lines. The present study was undertaken to verify the effect of nitrogen cold plasma pre-treatment conducted for 8 min (20 kHz) on the content of antioxidants, antioxidant activity, the profile of volatile compounds, microbial count, pH and color measured in herb extracts (12 herbs: Echinacea purpurea; Salvia officinalis; Urtica dioica; Polygonum aviculare; Vaccinium myrtillus; Taraxacum officinale; Hypericum perforatum; Achillea millefolium; Sanguisorba officinalis; Leonurus cardiaca; Ballota nigra; Andrographis paniculata) obtained with its usage. The surface morphology of extracted herbs was examined as well. Herbs used for extraction were ground and suspended in water before cold plasma treatment, which is a novel approach not studied before. Most plasma-treated extracts were characterized by a higher content of polyphenols (11 out of 12). Content of flavonoids and anthocyanins increased in four extracts and in the case of anthocyanins was significantly higher in comparison to control (up to 77%). The antioxidant activity measured at least by one method (ABTS, DPPH, FRAP) was also higher in nine plasma-treated solutions. Moreover, plasma decreased total aerobic bacteria, affected the color and increased pH of the extracts. The surface structure of the plant material after the extraction process was significantly damaged, which probably led to a higher extraction yield of bioactive compounds and in consequence to the higher antioxidant activity of extracts obtained with the cold plasma treatment.